2013
DOI: 10.3126/jkmc.v1i2.8150
|View full text |Cite
|
Sign up to set email alerts
|

Etiology of urinary tract infection and drug resistance cases of uropathogenes

Abstract: Background: Multidrug resistant bacterial isolates have been frequently reported from different parts of the world as emerging treatment problem. Objectives: The study was conducted to fi nd out etiology of urinary tract infection and drug resistance trend among clinical pathogens in urinary tract. Methods: Mid-stream urine samples from patients suspected of urinary tract infection were collected for routine culture and antibiotic susceptibility testing and were processed according to the standard laboratory m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 10 publications
9
13
0
Order By: Relevance
“…The results were in agreement with the ndings by many other investigators [28][29][30]. The close proximity of the vaginal and anal opening in the female and the absence of the prostatic uid which has the bactericidal property in the female may make them more susceptible to the UTIs [29,31]. The patients of age group (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) showed the highest signi cant growth i.e.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results were in agreement with the ndings by many other investigators [28][29][30]. The close proximity of the vaginal and anal opening in the female and the absence of the prostatic uid which has the bactericidal property in the female may make them more susceptible to the UTIs [29,31]. The patients of age group (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) showed the highest signi cant growth i.e.…”
Section: Discussionsupporting
confidence: 92%
“…The close proximity of the vaginal and anal opening in the female and the absence of the prostatic uid which has the bactericidal property in the female may make them more susceptible to the UTIs [29,31]. The patients of age group (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) showed the highest signi cant growth i.e. 44.49% which was similar to the study by Yadav The overall prevalence of UTI was 32.29% in diabetic patients and 15.97% in non-diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…E. coli, including other enterobacteria, are likely to have caused infection after colonization of the periurethral area by gastrointestinal tract flora [27]. This accords with other studies [21, 22, 24, 28-34]. However, discords with following studies [35-38].…”
Section: Discussionmentioning
confidence: 54%
“…The sex wise distribution ( Figure 2) showed that females (86.97%) were more susceptible than males (13.04%). Out of 51 samples, 23 samples showed the growth of E. coli which were subjected to biofilm productions by Congo red agar method among which 16 (70%) isolates showed the formation of biofilms [15]. All the biofilm producing UPEC were subjected to antibiotic susceptibility test [16,17] which showed maximum resistant towards erythromycin (100%) followed by amoxicillin (87.5%), cefotaxime (75%), levofloxacin (63%) and nitrofurantoin (12.5%).…”
Section: Resultsmentioning
confidence: 99%